Modified NASICON type solid electrolyte, preparation method and application in preparation of composite solid electrolyte membrane

By calcining argon and acidic treatment of NASICON type solid electrolytes, the oxygen vacancy and Lewis acidic sites are enhanced, and the problem of instability of the interface of the composite solid electrolyte is solved, significantly improving the lithium ion conductivity and the cycling performance of lithium batteries.

CN119852505APending Publication Date: 2025-04-18INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510056041.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-27
Filing Date
2025-01-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The interface instability between the inorganic and polymer components in the composite solid electrolyte results in low ion conductivity, limiting the performance of solid-state lithium batteries.

Method used

The number and strength of the oxygen vacancies and Lewis acidic sites are enhanced by calcining the NASICON type solid electrolyte under an argon atmosphere and chemically treating it with an acid solution, thereby improving the interface compatibility of the inorganic and polymer components.

Benefits of technology

The ion conductivity and lithium ion transmission capability of the composite solid electrolyte membrane are significantly improved, and the cyclic charging and discharge performance of solid lithium batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852505A_ABST
    Figure CN119852505A_ABST
Patent Text Reader

Abstract

The invention discloses a modified NASICON type solid electrolyte, a preparation method thereof and application of the modified NASICON type solid electrolyte in preparation of a composite solid electrolyte membrane. The preparation method comprises the following steps: firstly, calcining an NASICON type solid electrolyte in an inert gas atmosphere, then putting the NASICON type solid electrolyte into an acid solution for chemical treatment, washing and drying, and then preparing the organic-inorganic composite solid electrolyte membrane with polyvinylidene fluoride-hexafluoropropylene. According to the modification method, the oxygen vacancy concentration and the number of surface acid sites in the NASICON type solid electrolyte material can be remarkably improved, and the organic-inorganic phase interface compatibility is improved. The prepared composite electrolyte membrane has the characteristics of high ionic conductivity and capability of remarkably improving the cycle performance of the room-temperature solid-state lithium battery. The method is simple in process and excellent in performance, and has important practical significance and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state lithium batteries, and in particular to a modified NASICON solid-state electrolyte, a preparation method and an application thereof in preparing a composite solid-state electrolyte membrane. Background Art

[0002] As the global demand for clean energy and efficient energy storage technology continues to grow, lithium batteries have become the mainstream energy storage device due to their high energy density and long service life. However, the liquid electrolyte used in traditional lithium batteries has exposed a series of significant disadvantages during long-term use. For example, low thermal stability, easy leakage or combustion, greatly reducing the safety of the battery. In addition, the interface between the liquid electrolyte and the electrode material is unstable, which can easily lead to interfacial reactions and overall battery performance degradation. Solid-state batteries use solid electrolytes instead of liquid electrolytes, which have higher thermal stability and lower leakage risks. Therefore, they are considered to be the core of future high-energy-density and safer energy storage technologies.

[0003] Solid electrolytes are the core materials of solid-state batteries. At present, solid electrolytes are mainly divided into two categories: inorganic solid electrolytes and polymer electrolytes. Inorganic solid electrolytes, such as oxides, sulfides and halides, usually have high ionic conductivity and good thermal stability, which enables them to maintain excellent performance in high temperature environments. However, these inorganic materials often have strong brittleness, which may cause cracks or fractures during the charge and discharge process, affecting the long-term cycle performance and mechanical stability of the battery. In contrast, polymer electrolytes have good flexibility and processability, and can effectively alleviate the volume expansion and mechanical stress of the battery during charge and discharge. However, the ionic conductivity of polymer electrolytes is low at room temperature, which limits their application in high-performance solid-state batteries. Therefore, the composite solid electrolyte prepared by combining inorganic solid electrolytes and polymer electrolytes can combine the advantages of both and improve the ionic conductivity, mechanical stability and interface compatibility of the electrolyte.

[0004] Although composite solid electrolytes have many advantages in theory, in practical applications, low ionic conductivity is still one of the main constraints, which in turn limits the overall performance of solid-state batteries. Composite solid electrolytes are composed of two components, inorganic materials and polymers. Compatibility problems often occur at the interface after the composite. This mismatched interface structure will lead to the obstruction of ion transmission in the electrolyte, and also cause charge accumulation at the interface, further exacerbating the energy loss of the battery during the charge and discharge process, thereby significantly reducing the overall ionic conductivity. In addition, interface instability may also cause structural degradation or separation of polymers and inorganic materials during long-term circulation, thereby destroying the structural integrity of the composite electrolyte and affecting the cycle stability and charge and discharge efficiency of the battery. For example, patent CN114006028A discloses a modified inorganic fast ion conductor, which connects an organic carbon chain to an inorganic fast ion conductor through a chemical bond, and then prepares a composite solid electrolyte membrane with a polymer matrix by a casting method, which improves the interface compatibility between the inorganic phase and the organic phase. However, the ionic conductivity of the composite solid electrolyte membrane disclosed in the patent is limited, and it is necessary to maintain the charge and discharge cycle of the solid-state battery at a higher temperature. Patent CN112670561A discloses a method for improving surface defects of solid electrolytes and a method for preparing composite solid electrolyte membranes. This method uses a reaction solution composed of an acid, a lithium salt and a solvent to chemically etch the surface of a garnet-type solid electrolyte, thereby removing Li2CO3 impurities generated on the surface of LLZO when it is placed in the air. However, the method disclosed in this patent can only remove surface impurities generated by the garnet-type solid electrolyte itself, and does not affect the structure of the solid electrolyte itself, so the improvement of the compatibility of the organic-inorganic phase interface is very limited. Summary of the invention

[0005] In view of the problems mentioned in the background technology, the present invention proposes a method for modifying a NASICON-type solid electrolyte, and combines it with polyvinylidene fluoride-hexafluoropropylene to prepare a composite solid electrolyte membrane. Specifically, the NASICON-type solid electrolyte is calcined under an argon atmosphere, and then chemically treated with an acidic solution. The number of oxygen vacancies and the concentration of unpaired electrons in the obtained modified solid electrolyte powder are greatly improved, and the number and intensity of Lewis acid sites are significantly increased, which not only enhances the interfacial compatibility of inorganic components and polymer components through electrostatic interactions, but also promotes the dissociation of lithium salts, thereby enhancing the transmission of lithium ions in the electrolyte. The prepared composite electrolyte membrane has high ionic conductivity, and the assembled solid-state battery also has excellent cycle charge and discharge performance.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for preparing a modified NASICON solid electrolyte comprises the following steps:

[0008] (1) calcining NASICON solid electrolyte powder at high temperature in an argon atmosphere to obtain an intermediate product A;

[0009] (2) The intermediate product A obtained in step (1) is ball-milled to obtain B, and B is dispersed in an acidic solution and stirred, and after washing and drying, a modified NASICON-type solid electrolyte C is obtained.

[0010] Furthermore, the NASICON solid electrolyte in step (1) is Li 1+x Al x Ge 2-x (PO4)3(LATP) or Li 1+ x Al x Ti 2-x (PO4)3(LAGP), 0≤x≤2.

[0011] Furthermore, the calcination temperature of step (1) is 200-900° C., and the calcination time is 2-12 hours.

[0012] Furthermore, the ball milling speed in step (2) is 200-800 r / min, and the ball milling time is 2-20 h.

[0013] Furthermore, the solute of the acidic solution in step (2) is one or a mixture of two or more of hydrochloric acid, sulfuric acid, nitric acid, oxalic acid, phosphoric acid or acetic acid, the solvent is one or a mixture of two or more of methanol, ethanol, isopropanol, water, acetonitrile, N,N-dimethylformamide or N-methylpyrrolidone, and the concentration of the acidic solution is 0.01-1 mol / L.

[0014] The invention also provides a modified NASICON solid electrolyte prepared by the preparation method.

[0015] The present invention also provides the use of the modified NASICON solid electrolyte in the preparation of a composite solid electrolyte membrane, comprising the following steps: adding the modified NASICON solid electrolyte C in a certain proportion to a solution consisting of polyvinylidene fluoride-hexafluoropropylene, a lithium salt and an organic solvent, stirring and ultrasonically mixing the solution to obtain a composite solid electrolyte membrane, and then applying the solution on a glass plate with a scraper of a certain thickness, and vacuum drying the solution to obtain a composite solid electrolyte membrane.

[0016] Furthermore, the lithium salt in the step is one or a mixture of two or more of LiFSI, LiPF6, LiBOB, LiBF4 or LiTFSI, the mass of the lithium salt is 5%-100% of polyvinylidene fluoride-hexafluoropropylene, and the mass of the modified solid electrolyte powder is 1-50% of polyvinylidene fluoride-hexafluoropropylene.

[0017] Furthermore, the stirring time is 0.5-10h, and the ultrasonic time is 1-60min.

[0018] Furthermore, the scraper thickness is 50-1000 μm, the vacuum drying temperature is 50-150° C., and the vacuum drying time is 1-20 hours.

[0019] The composite solid electrolyte membrane prepared by the method described in the present invention is used in a solid-state lithium battery, specifically, as an electrolyte, and assembled with a lithium sheet negative electrode and a nickel-cobalt-manganese oxide positive electrode into a solid-state lithium battery.

[0020] Compared with the prior art, the present invention has at least the following beneficial effects:

[0021] 1. The present invention utilizes simple methods such as calcination in an argon atmosphere and chemical treatment with an acidic solution to modify the NASICON type solid electrolyte, thereby greatly increasing the number of oxygen vacancies and Lewis acid sites in its structure. 2. The particle size of the modified solid electrolyte powder is controlled within a reasonable range by ball milling, which can effectively improve the interface contact and reduce particle aggregation. 3. The composite solid electrolyte membrane prepared by using the modified solid electrolyte powder and polyvinylidene fluoride-hexafluoropropylene effectively improves the compatibility of the two-phase interface, promotes the dissociation of lithium salts, and has an anchoring effect on anions, thereby enhancing the transmission of lithium ions in the electrolyte, thereby improving the overall ionic conductivity. 4. Due to the above reasons, the composite solid electrolyte membrane prepared using the modified NASICON type solid electrolyte powder of the present invention is assembled into a solid-state battery, showing a higher discharge specific capacity and better cycle performance, with a 0.1C first discharge specific capacity>150mAh / g, and a 0.5C cycle capacity of 100 times maintained at more than 120mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the X-ray diffraction diagram of the NASICON solid electrolyte before and after modification described in Example 1 of the present invention.

[0023] Figure 2 This is the infrared spectrum of pyridine before and after modification of the NASICON solid electrolyte described in Example 1 of the present invention.

[0024] Figure 3 This is a scanning electron microscope image of the composite solid electrolyte membrane described in Example 1 of the present invention.

[0025] Figure 4 This is a cycle performance diagram of the composite solid electrolyte membrane described in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0027] Example 1

[0028] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0029] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 h in an argon atmosphere to obtain intermediate product A.

[0030] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C. Figure 1 is the XRD of solid electrolyte powder before and after modification, Figure 2 The infrared spectra of solid electrolyte powder pyridine before and after modification. The number and intensity of its Lewis acid sites are significantly enhanced.

[0031] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), then add modified NASICON solid electrolyte C (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours and then ultrasonicate for 30 minutes to obtain a suspension.

[0032] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane. Figure 3 This is the SEM image of the composite solid electrolyte membrane.

[0033] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.82mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was charged and discharged at 25°C and in the voltage range of 2.7-4.3V. The 0.1C first discharge capacity was 155mAh / g, and the capacity after 100 cycles at 0.5C was 120mAh / g. Figure 4 This is the cycle performance diagram of the composite solid electrolyte membrane.

[0034] Example 2

[0035] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0036] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 200°C for 3 h in an argon atmosphere to obtain intermediate product A.

[0037] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0038] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0039] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0040] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.46mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 120mAh / g, and the capacity after 100 cycles at 0.5C was 64mAh / g.

[0041] Example 3

[0042] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0043] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 900°C for 10 h in an argon atmosphere to obtain intermediate product A.

[0044] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0045] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0046] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0047] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.61mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 139mAh / g, and the capacity after 100 cycles at 0.5C was 86mAh / g.

[0048] Example 4

[0049] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0050] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 h in an argon atmosphere to obtain intermediate product A.

[0051] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in a 0.01 mol / L oxalic acid aqueous solution, stirred for 5 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0052] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0053] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0054] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.38mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 109mAh / g, and the capacity after 100 cycles at 0.5C was 47mAh / g.

[0055] Example 5

[0056] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0057] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 h in an argon atmosphere to obtain intermediate product A.

[0058] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in a 1 mol / L phosphoric acid aqueous solution, stirred for 60 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0059] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0060] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0061] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.27mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 87mAh / g, and the capacity after 100 cycles at 0.5C was 21mAh / g.

[0062] Example 6

[0063] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0064] (1) 2 g Li 1.5 Al 0.5 Ge1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 h in an argon atmosphere to obtain intermediate product A.

[0065] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0066] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (1% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0067] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0068] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.22mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 92mAh / g, and the capacity after 100 cycles at 0.5C was 56mAh / g.

[0069] Example 7

[0070] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0071] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 h in an argon atmosphere to obtain intermediate product A.

[0072] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0073] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (30% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0074] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0075] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.71mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 141mAh / g, and the capacity after 100 cycles at 0.5C was 107mAh / g.

[0076] Example 8

[0077] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0078] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 h in an argon atmosphere to obtain intermediate product A.

[0079] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0080] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (50% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0081] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0082] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.64mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 138mAh / g, and the capacity after 100 cycles at 0.5C was 100mAh / g.

[0083] Example 9

[0084] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0085] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 h in an argon atmosphere to obtain intermediate product A.

[0086] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0087] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0088] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 50° C. for 2 h to obtain a composite solid electrolyte membrane.

[0089] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.79mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 60mAh / g, and the capacity after 100 cycles at 0.5C was 25mAh / g.

[0090] Example 10

[0091] The preparation method of the modified solid electrolyte powder and the composite solid electrolyte membrane of this embodiment is as follows:

[0092] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 h in an argon atmosphere to obtain intermediate product A.

[0093] (2) The intermediate product A was ball-milled at 400 r / min for 10 h to obtain B, and B was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain a modified NASICON-type solid electrolyte C.

[0094] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified NASICON solid electrolyte C (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0095] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and vacuum dried at 150° C. for 12 h to obtain a composite solid electrolyte membrane.

[0096] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.13mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 43mAh / g, and the capacity after 100 cycles at 0.5C was 11mAh / g.

[0097] Comparative Example 1 (Only calcination is used on the basis of Example 1)

[0098] The preparation method of the modified solid electrolyte powder and the composite electrolyte membrane of this comparative example is as follows:

[0099] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly spread in a corundum crucible and calcined at 450°C for 6 hours in an argon atmosphere to obtain an intermediate product.

[0100] (2) The intermediate product was ball-milled at 400 r / min for 10 h to obtain a modified NASICON solid electrolyte.

[0101] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified solid electrolyte powder (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0102] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0103] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.49mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 111mAh / g, and the capacity after 100 cycles at 0.5C was 57mAh / g.

[0104] Comparative Example 2 (Only using acid treatment on the basis of Example 1)

[0105] The preparation method of the modified solid electrolyte powder and the composite electrolyte membrane of this comparative example is as follows:

[0106] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 After ball milling at 400 r / min for 10 h, (PO4)3 was uniformly dispersed in an aqueous solution of 0.6 mol / L oxalic acid and stirred for 15 min. The modified NASICON solid electrolyte was obtained after washing with ethanol and vacuum drying.

[0107] (2) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified solid electrolyte (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0108] (3) The suspension was evenly coated on a glass substrate using a 500 μm scraper and vacuum dried at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0109] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.61mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 123mAh / g, and the capacity after 100 cycles at 0.5C was 75mAh / g.

[0110] Comparative Example 3 (Li 1.5 Al 0.5 Ge 1.5 (PO4)3 powder (unmodified)

[0111] The preparation method of the solid electrolyte powder and the composite electrolyte membrane of this comparative example is as follows:

[0112] (1) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene) and Li (15% by weight of polyvinylidene fluoride-hexafluoropropylene) 1.5 Al 0.5 Ge 1.5 (PO4)3, stirred for 4 h and then ultrasonicated for 30 min to obtain a suspension.

[0113] (2) The suspension was evenly coated on a glass substrate using a 500 μm scraper and vacuum dried at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0114] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.34mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 96mAh / g, and the capacity after 100 cycles at 0.5C was 63mAh / g.

[0115] Comparative Example 4 (Based on Example 1, acid treatment followed by calcination)

[0116] (1) 2 g Li 1.5 Al 0.5 Ge 1.5 (PO4)3 was evenly dispersed in an aqueous solution of 0.6 mol / L oxalic acid, stirred for 15 min, washed with ethanol and vacuum dried to obtain an intermediate product.

[0117] (2) The obtained intermediate product was evenly spread in a corundum crucible, calcined at 450°C for 6 h in an argon atmosphere, and then ball-milled at 400 r / min for 10 h to obtain a modified NASICON-type solid electrolyte.

[0118] (3) Dissolve polyvinylidene fluoride-hexafluoropropylene in N,N-dimethylformamide, add LiTFSI (60% by weight of polyvinylidene fluoride-hexafluoropropylene), add modified solid electrolyte (15% by weight of polyvinylidene fluoride-hexafluoropropylene), stir for 4 hours, and then ultrasonicate for 30 minutes to obtain a suspension.

[0119] (4) The suspension was evenly coated on a glass substrate using a 500 μm scraper and dried under vacuum at 60° C. for 5 h to obtain a composite solid electrolyte membrane.

[0120] The composite solid electrolyte membrane was used as the electrolyte, and the ionic conductivity was measured to be 0.73mS / cm using the blocking electrode method. Metal lithium was used as the negative electrode material of the battery, and nickel cobalt manganese oxide was used as the positive electrode material. The assembled battery was subjected to charge and discharge tests at 25°C and a voltage range of 2.7-4.3V. The initial discharge capacity at 0.1C was 136mAh / g, and the capacity after 100 cycles at 0.5C was 87mAh / g.

[0121] The performance test results of Example 1 and Comparative Examples 1-4 are shown in Table 1.

[0122] Table 1 Performance test results of embodiments and comparative examples

[0123]

[0124] The present invention modifies the NASICON type solid electrolyte by simple calcination and acid treatment, thereby enhancing the oxygen vacancy concentration and the number and strength of Lewis acid sites on its surface. The synergistic effect of the two can directly enhance the compatibility of the organic-inorganic interface through electrostatic attraction, etc. Although the single oxygen vacancy and Lewis acid site also have a certain optimization effect on the interface, the synergistic effect of the two can make it more tightly combined. In addition, the migration of lithium ions at the phase interface is enhanced, the lithium ion conductivity of the composite solid electrolyte membrane is improved, and the cycle performance of the battery is significantly improved when used in a room temperature solid lithium battery.

[0125] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a modified NASICON solid electrolyte, characterized in that: The steps include: (1) calcining NASICON solid electrolyte powder at high temperature under argon atmosphere to obtain intermediate product A; (2) The intermediate product A obtained in step (1) is ball-milled to obtain B, and B is dispersed in an acidic solution and stirred, and after washing and drying, a modified NASICON-type solid electrolyte C is obtained.

2. The NASICON type solid electrolyte modification method according to claim 1, characterized in that: The NASICON solid electrolyte in step (1) is Li 1+x Al x Ge 2-x (PO4)3 (LATP) or Li 1+x Al x Ti 2-x (PO4)3(LAGP), 0≤x≤2.

3. The NASICON type solid electrolyte modification method according to claim 1, characterized in that: The calcination temperature of step (1) is 200-900° C., and the calcination time is 2-12 hours.

4. The NASICON type solid electrolyte modification method according to claim 1, characterized in that: The ball milling speed in step (2) is 200-800 r / min, and the ball milling time is 2-20 h.

5. The NASICON type solid electrolyte modification method according to claim 1, characterized in that: The solute of the acidic solution in step (2) is one or a mixture of two or more of hydrochloric acid, sulfuric acid, nitric acid, oxalic acid, phosphoric acid or acetic acid, and the solvent is one or a mixture of two or more of methanol, ethanol, isopropanol, water, acetonitrile, N,N-dimethylformamide or N-methylpyrrolidone, and the concentration of the acidic solution is 0.01-1 mol / L.

6. A modified NASICON solid electrolyte obtained according to the preparation method according to any one of claims 1 to 5.

7. Use of the modified NASICON solid electrolyte according to claim 6 in preparing a composite solid electrolyte membrane, characterized in that The following steps are involved: The modified NASICON solid electrolyte C is added to a solution consisting of polyvinylidene fluoride-hexafluoropropylene, lithium salt and organic solvent in a certain proportion, stirred and ultrasonically mixed evenly, then coated on a glass plate with a scraper of a certain thickness, and vacuum dried to obtain a composite solid electrolyte membrane.

8. The use according to claim 7, characterized in that: The lithium salt in the step is one or a mixture of two or more of LiFSI, LiPF6, LiBOB, LiBF4 or LiTFSI, the mass of the lithium salt is 5%-100% of polyvinylidene fluoride-hexafluoropropylene, and the mass of the modified solid electrolyte powder is 1-50% of polyvinylidene fluoride-hexafluoropropylene.

9. The use according to claim 7, characterized in that: The stirring time is 0.5-10h, and the ultrasonic time is 1-60min.

10. The use according to claim 7, characterized in that: The scraper thickness is 50-1000 μm, the vacuum drying temperature is 50-150° C., and the vacuum drying time is 1-20 hours.

Citation Information

Patent Citations

  • Surface defect improvement method for solid electrolyte and preparation method for composite solid electrolyte membrane

    CN112670561A